IMPLEMENTASI GOOGLE LOOKER STUDIO UNTUK ANALISIS TREN DAN VISUALISASI DATA (STUDI KASUS: PRODUKSI PADI PULAU SUMATERA) - Hesananda, Rizki; Faizal Racma, Dhany (Innotech: Jurnal Ilmu Komputer, Sistem Informasi dan Teknologi Informasi, 2024)
This study analyzes rice production outcomes in Sumatra Island from 1995 to 2020 using data obtained from Kaggle and the Indonesian Agency for Meteorology, Climatology, and Geophysics (BMKG). The dataset includes annual rice production, harvested area, and climate variables such as rainfall, humidity, and average temperature. Analysis was conducted using Google Looker Studio to generate various visualizations facilitating data interpretation. The findings reveal that North Sumatra Province has the highest rice production, followed by South Sumatra and Lampung. While rainfall does not consistently correlate with rice production, a strong relationship was observed between harvested area and rice yields, underscoring the importance of efficient land management and agricultural practices. The study also identifies a decline in rice production across provinces since 2017. Limitations include the restricted data period up to 2020 and the exclusion of variables such as government policies and agricultural technology. Future research should expand data coverage, consider additional variables, and employ advanced predictive model.